Analisis Pengaruh Investasi Dalam Negeri dan Tenaga Kerja Terhadap Pertumbuhan Ekonomi di Kabupaten Manokwari Tahun 2020-2023 - Zarlin, Zarlin; Tafalas, Muhammad Guzali; Semet, Maria Magdalena (Lensa Ekonomi, 2024)
This research aims to find out whether investment and labor have an effect on economic growth in Manokwari Regency in the period 2020 to 2023. This research was carried out using quantitative analysis methods with testing techniques through (1) Classical assumption tests, in the form of normality tests, multicollinearity tests, heterodasticity; (2). Multiple linear regression test, and (3). Hypothesis Test, in the form of Partial Test (T-Test), Simultaneous Test (F-Test) and Determination Coefficient Test (R²). From the results of research conducted, the investment variable has a significant effect on economic growth, while the labor variable has no significant effect on economic growth in Manokwari Regency and simultaneously the investment and labor variables have a significant effect on economic growth.